New trends in the physics and mechanics of biological systems : Ecole de physique des Houches ; session XC, 6-31 July 2009 - n; Ben Amar, M. (Oxford : Oxford University Press, 2011)
This text presents the latest trends in the modelling of biological systems from a mechanics perspective. It covers both fluid and solid mechanics, the modelling of growth in biological systems, and presents the application of physical methods for the modelling of systems in cellular biology, physiology and morphogenesis.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Biological systems -- Mathematical models -- Congresses